Evaluation on the Effectiveness of Visual Learning Environment on Programming Course From Students’ Perspectives - Dina, Nasa Zata; Wuryanto, Eto; Marjianto, Rachman Sinatriya (IIUM Engineering Journal, 2019)
ABSTRACT: This paper discusses the effectiveness of visual learning environment which is used to help students in university to study programming course. The visual learning environment which is used in this study is Greenfoot and Alice. The main goal of this article is to obtain the correlation between students‘ satisfaction level and their grades in studying programming course using visual learning environment tools. The participants were conducted on 110 students who took programming course during their first year. A survey was sent to students about their satisfaction level in learning programming course. Two-variable correlation analysis, significance test and descriptive analysis were conducted to find out the relationship between students’ learning satisfaction level and their grades in programming course. This study discusses the student perspectives that are summarized in ten questions. There is a significant correlation between independent and dependent variables. The ? value is 2.09 which proves that the independent variable in the form of student’s learning satisfaction level is useful to obtain better assessment of their grades. Based on their perspectives, it is found that visual learning environment tools have more significant influence in improving the students‘ grade than traditional learning method. Further research is needed to find out other impact factors. ABSTRAK: Makalah ini membincangkan keberkesanan persekitaran pembelajaran visual yang digunakan untuk membantu pelajar di universiti untuk mempelajari kursus pengaturcaraan. Persekitaran pembelajaran visual yang digunakan dalam kajian ini ialah Greenfoot dan Alice. Matlamat utama artikel ini adalah untuk mendapatkan korelasi antara tahap kepuasan pelajar dan gred mereka dalam mengkaji kursus pengaturcaraan menggunakan alat-alat persekitaran pembelajaran visual. Para peserta telah diadakan pada 110 orang pelajar yang mengambil kursus pengaturcaraan pada tahun pertama mereka. Satu tinjauan telah dihantar kepada pelajar tentang tahap kepuasan mereka dalam pembelajaran kursus pengaturcaraan. Analisis korelasi dua-pembolehubah, ujian penting dan analisis deskriptif telah dijalankan untuk mengetahui hubungan antara tahap kepuasan belajar pelajar dan gred mereka dalam kursus pengaturcaraan. Kajian ini membincangkan perspektif pelajar yang diringkaskan dalam sepuluh soalan. Terdapat korelasi yang signifikan antara pembolehubah bebas dan bergantung. Nilai ? ialah 2.09 yang membuktikan bahawa pemboleh ubah bebas dalam bentuk tahap kepuasan pembelajaran pelajar adalah berguna untuk mendapatkan penilaian yang lebih baik dari gred mereka. Berdasarkan perspektif mereka, didapati alat persekitaran pembelajaran visual mempunyai pengaruh yang lebih besar dalam meningkatkan gred pelajar daripada kaedah pembelajaran tradisional. Kajian lanjut diperlukan untuk mengetahui faktor-faktor kesan yang lain.